Socio-Economics of the Community with Land Transportation in Namtabung Village, Selaru District, Tanimbar Islands Regency - Betoky, Meriane; Leuwol, Ferdinad Salomo; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
The economic development of a country is often measured by economic growth, which is an indicator of the success of development. National development aims to improve the welfare of society, which can be achieved through economic growth. Social and economic factors are interrelated, with the position of individuals in society being influenced by economic factors, education level, and income. Modes of transportation, such as asphalt roads, play an essential role in the economic development of society by increasing accessibility. In 2015, the Namtabung village government collaborated with the provincial government to build an asphalt road, which has since improved connectivity between villages, reduced economic limitations and accelerated the growth of the village economy. This study carries a qualitative method with a descriptive approach, involving interviews and observations as the primary data sources. Researchers are actively involved in the events or situations being studied, creating a deep understanding. Descriptive qualitative research methods investigate research objects in a natural context or actual situation without experimental manipulation. The population consists of 15 members of the Namtabung village community who have or do not have a mode of transportation. The sample was selected by simple random sampling, taking five people from 3 RTs to get 15 community samples. This approach allows researchers to gain in-depth insight into the impact of transportation modes on the daily lives of the Namtabung village community. The construction of asphalt roads and transportation modes in Namtabung Village has positively impacted social and economic aspects. Education, health, housing, and community income have increased significantly. The agricultural and fisheries sectors have also developed with adequate transportation, even to neighboring villages. Land transportation facilitates the sale of products, improves mobility, and supports access to education and health services.